Measuring the Impact of Oil Prices and Exchange Rate Shocks on Inflation: Evidence from India - Akhil SHARMA; Abdul RISHAD; Sanjeev GUPTA (Eurasian Journal of Business and Economics, 2019)
The purpose of this study is to examine the long-run and short-run impact of crude oil price and exchange rate shocks on domestic inflation in India within the framework of the Autoregressive Distributed Lag (ARDL) model. The results show that the exchange rate and oil price shocks significantly influence domestic inflation during the study period (April 1994 to February 2018). Further, the breakpoint unit root test revealed the severe impact of the 2008 financial crisis on inflation in India. The findings show that any move to scale down fuel subsidies will escalate cost-push inflation severely, as the country is an energy-dependent economy. So, policymakers shall stabilise the impact of these shocks through suitable monetary policy actions.